2011
DOI: 10.1016/j.cell.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Human Endogenous Coregulator Complexome

Abstract: Summary Elucidation of endogenous cellular protein-protein interactions and their networks is most desirable for biological studies. Here we report our study of endogenous human coregulator protein complex networks obtained from integrative mass spectrometry-based analysis of 3,290 affinity purifications. By preserving weak protein interactions during complex isolation and utilizing high levels of reciprocity in the large dataset we identified many unreported protein associations, such as a transcriptional net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
407
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 393 publications
(428 citation statements)
references
References 68 publications
18
407
1
2
Order By: Relevance
“…Consistent with the classical definition of a transcriptional coactivator as an amplifier and stabilizer of coregulator complexes (2,9,10,14,15), loss of SRC-2 strikingly reduced the recruitment of metabolically responsive proteins to both Gck and G6pc promoters (Fig. 3C).…”
Section: Src-2 Recruits Distinct Coregulator Complexes To Regulate Gcsupporting
confidence: 58%
See 2 more Smart Citations
“…Consistent with the classical definition of a transcriptional coactivator as an amplifier and stabilizer of coregulator complexes (2,9,10,14,15), loss of SRC-2 strikingly reduced the recruitment of metabolically responsive proteins to both Gck and G6pc promoters (Fig. 3C).…”
Section: Src-2 Recruits Distinct Coregulator Complexes To Regulate Gcsupporting
confidence: 58%
“…supports this notion (9). The dynamic interaction of multiple protein networks is collectively referred to as the "interactome," and it is acutely responsive to cellular signaling cues (10).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…We find that multiple genetic targets of BRD4-NUT or ZNF532-NUT, including ZNF532 and ZMYND8, encode components of BRD4 regulatory complexes. Interestingly, it was previously reported that ZMYND8/ZNF532/ZNF592/ZNF687 interact with each other as a central hub in a large transcriptional network (26,30). ZMYND8 has several important chromatin-binding domains (bromodomain, PWWP, PHD finger, MYND), and can function as a combinatorial reader of histone modifications such as H3K4me1 and H3K14ac (31).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, nuclear hormone receptors have been shown to associate with upward of 10,000 "coregulatory" proteins (73), yet the complete ER␤ interactome has not been described. The data herein contribute to our understanding of the ER␤ interactome in the brain and also quantify ER␤-protein interactions as a function of age.…”
Section: Discussionmentioning
confidence: 99%